Pengembangan Media Permainan MONAYA untuk Meningkatkan Pemahaman Multikultural Anak Usia 7-8 Tahun - Firdausi, Melisa Indah; Hapidin, Hapidin; Tarwiyah, Tuti (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
The purpose of this study is to improve the multicultural understanding of children aged 7-8 years through the MONAYA game media. MONAYA's game media is a game of Cultural Monopoly which has content of cultural or multicultural diversity and has printed on large banners and makes children as pawns using dice and supporting cards of large size so as to attract children's interest in teaching and learning activities and become wrong an alternative learning media. This study uses ADDIE (Analyze, Design, Develop, Implement, Evaluate) methods and has been tested through one-on-one trials), small group trials and field group trials and has been validated by early childhood education experts, media experts and multicultural experts. There is an increase in the results of very high child pre-test and post-test and enthusiastic activities which indicate that the MONAYA game media is suitable to be used to increase multicultural understanding of children aged 7-8 years.